Satellite imagery reveals increasing volatility in human night-time activity - Tian Li; Zhuosen Wang; Christopher C. M. Kyba; Miguel O. Román; Karen C. Seto; Yun Yang; Shi Qiu; Theres Kuester; Michail Fragkias; Xiang Chen; Thomas H. Meyer; Chadwick D. Rittenhouse; et al. (Nature, 2026)
Abstract Artificial light at night (ALAN) marks the global impact of humanity 1,2 . Yet, our understanding of its true ebb and flow has been limited, often based on temporally aggregated satellite data that obscure finer dynamics. Here, using daily night-time satellite imagery 3 and a continuous change detection approach 4,5 , we created global maps of high-frequency ALAN dynamics (2014–2022). Our findings challenge the prevailing perspective that changes in light radiance are largely gradual and unidirectional. Instead, the nightlights of Earth are surprisingly dynamic, characterized by frequent and coexisting brightening and dimming. On average, each location experiencing change underwent 6.6 distinct shifts over the 9 years. Driven by this volatility, the cumulative area of total ALAN change comprised 2.05 million km 2 of abrupt changes and 19.04 million km 2 of gradual changes. Brightening contributed a radiance increase equivalent to 34% of the 2014 global baseline, whereas dimming offset this by 18%. Notably, both brightening and dimming have markedly intensified over the past decade. This evidence of increasing volatility in human night-time activity provides an important dynamic dimension for understanding urban evolution, energy transitions, policy impacts and ecological consequences of rapidly changing illuminated nights.